Sweets for my sweet: The impact of partner unemployment on individual physical health - Giovanni Gallo; Michele Ubaldi (Global Labor Organization (GLO), 2025)
This paper investigates the effect of partner unemployment on individual physical health. Using data from two nationally representative Italian surveys of households and employing partial identification to address endogenous selection into unemployment, we show that the impact of partner unemployment on individual physical health is related to the role of the unemployed within the household. We document a null effect when the spouse is unemployed, whereas we find a negative health effect when the household head is unemployed. The negative effect of household head unemployment may be explained by a larger budget constraint and a consequent change in the dietary habits involving all household members. In particular, we highlight a decline in the quality of food consumption in the household when the household head is unemployed.
Keywords: D12; I10; J12; J60; 330; Unemployment; dietary habits; consumption; food quality; body mass index